Temporally Adrift and Permanently Liminal: Relations, Distalgia and a U.S. University as Site of Transition and Frontier - Frank G. Karioris (Culture Unbound: Journal of Current Cultural Research, 2016)
This article seeks to explore temporal reconceptualizations and forms of nostalgia that first-year university men are experiencing and creating. It will explore the ways that time can be conceived of in relation to the present and a future that is not-yet-existent. The article takes as its starting point ethnographic fieldwork in the 21st century at a private, Catholic university in the U.S. and, in particular, men in an all-male residence hall. In focusing on this hall, it means to locate and localize the thinking in the context of the 21st century as well as within the U.S., including neoliberalism as a social and economic method of relating. Through the exploration of these men’s envisioning of themselves as their future selves and the way they review the self that is now, this article makes a claim that they are – through both their actions, ways of relating, and the societal positioning – multiply liminal. Further, it will explore the way that through this temporal representation they are endowing themselves as permanently liminal both currently and in the future. The article situates these men amidst the university as an institution, as well as seeking to elucidate the importance of this temporal creation as a building of forms of transition and frontier.